Dampak Kenaikan Harga Bahan Bakar Minyak (BBM) Terhadap Keberlangsungan Bisnis Masyarakat Ditinjau Dari Perspektif Bisnis Islam - Fuadi, Fatih; Rizkiyah, Dara (CV ODIS, 2024)
The increase in fuel prices makes the sustainability of micro-enterprise businesses unstable. One of the factors causing instability is inflation that occurs in regions in Indonesia, especially in Bandar Lampung. Inflation occurred at the same time as fuel prices increased. This impacts the sustainability of the community's micro-enterprise businesses. The micro businesses that are run are a bridge to meet economic needs. The formulation of the problem in this research is 1) What is the impact of the increase in fuel prices on the sustainability of micro-enterprise businesses in Sukarame Bandar Lampung? 2) How will the community's efforts to increase fuel prices affect the sustainability of micro-businesses in Sukarame Bandar Lampung? 3) What is the perspective of Islamic business economics regarding the increase in fuel prices on business sustainability? To know the impact, efforts and perspectives of Islamic businesses on increasing fuel prices on business sustainability. The methodology used is a descriptive qualitative approach. Research location at micro businesses in Sukarame District, Bandar Lampung. The population in the study was 116,615 all micro businesses in Sukarame sub-district. And obtained 10 trusted informants. Data collection techniques use participant observation, interviews, and documentation. Data analysis with stages of data collection, data reduction, concluding, and research validation. The results of the research show that the impact of an increase in fuel prices on the sustainability of micro-enterprise businesses is a decrease in business productivity, decreased profits and loss of jobs. The types of businesses that experienced a big influence were culinary, grocery and transportation. Efforts made by the community are to increase the amount of time doing business than before. And people also save more in other ways Use fuel as needed. The Islamic view of business sustainability in this research is towards benefits supported by the state for the welfare of society. Benefits can be felt in the form of subsidized fuel oil